The Necessity of Value Education According to the Opinions of Pre-service Primary Teachers and Functionality of Life Science Course - Aslı Gündoğan (Anı Publishing, 2020)
The aim of this study was to determine the necessity of value education and functionality of pre-service primary teachers of life science course. Research was designed in the basic qualitative research methods. 60 pre-service primary teachers from the department of primary school teaching at a public university participated in the study. Research data were collected through open-ended questionnaires and daily plans; those were analyzed by content analysis method. According to the results, pre-service primary teachers found value education necessary in terms of individual, social, educational and universal. They explained the value education in the life science course in terms of its suitability to the nature of the course, its contribution to the child and society, problems and suggestions. Pre-service primary teachers think that there should be values of love, respect, patriotism and responsibility. They included responsibility and sensitivity in their daily plans and prefered to teach values through value transfer approach.